The Effects of Music Programme on Language Abilities of Typical and Atypical Preschoolers: A Case Study Series in Sarawak - TeeNa, Sim (Journal of Cognitive Sciences and Human Development, 2023)
Language delay is among the foremost common developmental difficulties related to adverse long-term educational outcomes, health, and well-being of people. While studies have indicated that music-making activities benefit preschoolers' language acquisition, little is known about how teacher-led music-based language enhancement programmes can be successfully adapted into local preschools for children with and without language delay. This research aims to determine if a complementary solution for training preschool teachers to lead a new programme—the Music-Based Language Enhancement Programme (MBLP©)—may positively enhance the language skills of preschoolers with and without language delays. Implementing this strategy has the potential to be an effective and sustainable approach to addressing real-world challenges in preschool settings. This research used multiple research methods and data collection approaches to address the research questions under three phases conducted at one preschool, which practised inclusion. Phase 1 sought to examine the feasibility of training non-music specialist preschool teachers in delivering the MBLP© and the acceptability of MBLP© implementation by stakeholders such as teachers (n = 4), preschoolers from cohort 2021 (n 11), the principal (n = 1), and parents (n = 11) in the preschool. The findings suggested that the MBLP© was feasible for teacher training. The programme was also acceptable by teachers, preschoolers, the principal, and parents. Phases 2 and 3 recruited three teachers and nine preschoolers (cohort 2022) from the same preschool. Phase 2 examined the pre- and post-differences in teachers' music teaching self-efficacy before and after teacher training and monitored the delivery performance during and after practicum with interactive reflection. Instruments used for these measures are 1) the Teacher Training Questionnaire and 2) MBLP© Delivery Performance Observation Scale. The results showed that the teachers' music teaching self-efficacy and the quality of MBLP © delivery improved. Phase 3 assessed the effect of thrice weekly MBLP© lessons on the language skills of preschoolers with and without language delays. The instruments in Phase 3 included 1) the New Reynell Developmental Language Scale (pre-post), 2) the SALTMusic scale (observational monitoring of preschoolers' social interaction, verbalisation, well-being, involvement, and music-making), and 3) the Smiley Face Likert Scale (feedback of the preschoolers’ satisfaction with the MBLP©). Results on the language skills enhancement, social interaction, verbalisation, well-being, involvement, and music-making were positive but nuanced. Observation data suggested that repeated chanting, singing, and movement provided enjoyable music-making in assimilating vocabulary syntax and encouraging words expression in sentences, which likely helped enhance language skills through the MBLP© lessons. The findings from this study have contributed preliminary empirical evidence about the potential benefits of teacher-led music-based language intervention on the enhancement of language skills among preschoolers with and without language delays. A primary limitation of the present study is that the data only represent preschoolers from one socioeconomic class, namely, middle-class families. Further research is needed to ascertain the generalisability of the MBLP©'s effectiveness in addressing language issues in preschoolers of different socioeconomic statuses.